Comparison of the Efficacy of Local Anesthesia Methods and Caudal Regional Anesthesia in Prostate Biopsy Applied Under Transrectal Ultrasonography: A Randomized Controlled Study - Pasali, Sahin; Ozden, Cuneyt; Kizilkan, Yalcin; Camgoz, Suleyman; Baskan, Semih; Senel, Samet; Demirel, Doruk; Gokkaya, Cevdet Serkan (Urology Journal, 2020)
Purpose: To evaluate the efficacy of caudal regional anesthesia and local anesthesia methods in prostate biopsy applied under transrectal ultrasonography. Matherials and Methods: This prospective study included a total of 160 patients randomly separated into 4 equal groups as intrarectal local anesthesia (IRLA), periprostatic local anesthesia (PPLA), combined local anesthesia (IRLA+PPLA), and caudal regional anesthesia (CRA). The patients were evaluated using the pain scores on a visual analog scale. Results: The pain score during anesthesia induction was significantly higher in the CRA group than in the IRLA and IRLA+PPLA groups (p<0.001). The pain score during entry of the probe to the rectum and movement was significantly lower in the CRA group than the IRLA groups (p=0.014). The pain score on penetration of the needle to the prostate and at 30 mins after the biopsy was significantly higher in the IRLA group (p<0.001). At 2 hours after the biopsy, the pain score in the CRA group was significantly lower than IRLA groups (p=0.015). Conclusion: The PPLA alone can be applied more quickly than CRA, causes less pain during the application, and has similar efficacy in reducing pain during and after the prostate biopsy procedure.